2015
DOI: 10.1038/bmt.2015.279
|View full text |Cite
|
Sign up to set email alerts
|

A preclinical acute GVHD mouse model based on chemotherapy conditioning and MHC-matched transplantation

Abstract: Animal disease models have been criticized for lack of resemblance to human illnesses, hampering transfer of knowledge from preclinical research to clinical medicine. In the field of allogeneic hematopoietic stem cell transplantation (allo-HSCT), it is standard practice to study GVHD in lethal TBI-based murine models. Frequently, MHC-mismatched donors are used in GVHD models. In contrast, in clinical allo-HSCT conditioning with chemotherapy (+/ − TBI) is common and donors are often MHC-matched. Aiming at a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 47 publications
3
44
0
Order By: Relevance
“…This model was developed to more closely mimic the clinical situation, where patients usually are MHC matched. With this model, similar T cell infiltration, GvHD-specific damage, and systemic inflammation were observed in the mice as reported in humans (273). Thus, animal models of selective mHA mismatch may represent human HSCT more closely than MHC-mismatched models (193).…”
Section: Advantages and Limitations Of Animal Models For Gvhdsupporting
confidence: 82%
“…This model was developed to more closely mimic the clinical situation, where patients usually are MHC matched. With this model, similar T cell infiltration, GvHD-specific damage, and systemic inflammation were observed in the mice as reported in humans (273). Thus, animal models of selective mHA mismatch may represent human HSCT more closely than MHC-mismatched models (193).…”
Section: Advantages and Limitations Of Animal Models For Gvhdsupporting
confidence: 82%
“…To analyze target organ damage we a minor mismatch GVHD model (LP→B6) [16] and applied histopathological scores after Lerner et al [17] At day +17, we found significantly reduced histopathological GVHD scores in liver, colon and skin in EGCG treated allo-BMT recipients vs. controls without EGCG treatment (Fig 3A). In the liver, untreated control allo-BMT recipients had GVHD-associated massively increased periportal infiltration of leukocytes whereas in EGCG treated allo-BMT recipients, infiltration was only slightly increased (Fig 3B).…”
Section: Resultsmentioning
confidence: 97%
“…Both models have been described previously. [9, 16] Allo-BMT recipients received a combination of 25mg/kg EGCG (Enzo Life Sciences, Lörrach, Germany) and 1mg/kg quercetin (Sigma Aldrich) dissolved in DMSO (20μl total) and PBS i.p. daily or EGCG and quercetin alone (for clinical score) or DMSO only (20μl, control) respectively from day 0 to end of experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the publication of Sadeghi et al [14], in which all mice died within 60 days (median survival = 11 days) after transplantation, the Bu-Cy conditioning regimen in our study resulted in more uniform survival of aGVHD mice. Of note, Riesner et al [24] have showed a delayed aGVHD in a murine MHC-matched, miHA-mismatched model [LP/J (H2k b ) →C57BL/6(H2k b )] using Bu (100 mg/kg)-Cy (300 mg/kg) conditioning. These discrepancies between our study and previous publications may be due to the degree of allomismatch (MHC-mismatched or miHA-mismatched), differences in graft (bone marrow cells and splenocytes), and the intensity of conditioning.…”
Section: Discussionmentioning
confidence: 99%